Three discourses on imagined occasions - Kierkegaard, Søren, 1813-1855.; Hong, Howard V. (Howard Vincent), 1912-2010.; Hong, Edna H. (Edna Hatlestad), 1913-2007. (Princeton, N.J. : Princeton University Press, 2009)
Three Discourses on Imagined Occasions was the last of seven works signed by Kierkegaard and published simultaneously with an anonymously authored companion piece. Imagined Occasions both complements and stands in contrast to Kierkegaard's pseudonymously published Stages on Life's Way. The two volumes not only have a chronological relation but treat some of the same distinct themes. The first of the three discourses, ""On the Occasion of a Confession,"" centers on stillness, wonder, and one's search for God--in contrast to the speechmaking on erotic love in ""In Vino Ve.
Cover; Title; Copyright; CONTENTS; HISTORICAL INTRODUCTION; Three Discourses on Imagined Occasions; Preface; On the Occasion of a Confession; On the Occasion of a Wedding; At a Graveside; SUPPLEMENT; Key to References; Original Title Page of Three Discourses on Imagined Occasions; Selected Entries from Kierkegaard's Journals and Papers Pertaining to Three Discourses on Imagined Occasions; EDITORIAL APPENDIX; Acknowledgments; Collation of Three Discourses on Imagined Occasions in the Danish Editions of Kierkegaard's Collected Works; Notes; Bibliographical Note; Index
Includes bibliographical references (p. [159]-[171]) and index.
OCLC control number change - Master record variable field(s) change: 050, 072, 082, 650
Keywords: Christian life -- Lutheran authors; Christianity; Kierkegaard, Soren, -- 1813-1855. -- Forord; Christian life -- Lutheran authors; God (Christianity) -- Worship and love; Marriage -- Religious aspects -- Christianity; Death -- Religious aspects -- Christianity; RELIGION / Christian Life / General; Christian life -- Lutheran authors; Death -- Religious aspects -- Christianity; God (Christianity) -- Worship and love; Marriage -- Religious aspects -- Christianity; PHILOSOPHY / Religious; Electronic books